ILLOCUTIONARY ACTS AND REPRESENTATIVE FUNCTION ON ENGLISH SPEECHES YOUTUBE CHANNEL - Anggi Permana Sidik; Pepen Priyawan; Erlan Aditya Ardiansyah (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study aims to figure out the kinds of illocutionary acts and furthermore the function of representative performed by the inspirations of American motivators in the persuasive recordings in the English Speeches Youtube channel. This research is a qualitative descriptive study. The subjects of this examination are four videos from notable inspirations from America in English Speeches YouTube channel. In the wake of posting, choosing, and gathering the videos, the videos were watched a few times to facilitate the scientist in interpreting them. In dissecting the information, the researcher just takes utterances that permit the motivators to pass their expectations on to the audience members. The illocutionary act information performed by the motivators were arranged utilizing the instrument following Searle's hypothesis and the functions of representative performed by the motivators were grouped utilizing the instrument following Searle's hypothesis too. The main tracking down shows five sorts of illocutionary acts performed by motivators, specifically representative, directive, commissive, declarative and expressive. The subsequent tracking down shows every one of the six sorts of representative functions performed by the inspiration motivators are claiming, predicting, stating, reporting, describing, and complaining. By performing five sorts of illocutionary acts, motivators might have different approaches to communicating their expectations to audience members. In the interim, motivators can likewise do different ways to fulfill the motivation behind their demeanor through the function of representative.